Apolipoprotein E mimetic peptide, CN‐105, improves outcomes in ischemic stroke. Issue 4 (9th March 2017) - Tu, Tian Ming; Kolls, Brad J.; Soderblom, Erik J.; Cantillana, Viviana; Ferrell, Paul Durham; Moseley, M. Arthur; Wang, Haichen; Dawson, Hana N.; Laskowitz, Daniel T.
Abstract: Objective: At present, the absence of a pharmacological neuroprotectant represents an important unmet clinical need in the treatment of ischemic and traumatic brain injury. Recent evidence suggests that administration of apolipoprotein E mimetic therapies represent a viable therapeutic strategy in this setting. We investigate the neuroprotective and anti‐inflammatory properties of the apolipoprotein E mimetic pentapeptide, CN‐105, in a microglial cell line and murine model of ischemic stroke. Methods: Ten to 13‐week‐old male C57/BL6 mice underwent transient middle cerebral artery occlusion and were randomly selected to receive CN‐105 (0.1 mg/kg) in 100 μ L volume or vehicle via tail vein injection at various time points. Survival, motor‐sensory functional outcomes using rotarod test and 4‐limb wire hanging test, infarct volume assessment using 2, 3, 5‐Triphenyltetrazolium chloride staining method, and microglial activation in the contralateral hippocampus using F4/80 immunostaining were assessed at various time points. In vitro assessment of tumor necrosis factor‐alpha secretion in a microglial cell line was performed, and phosphoproteomic analysis conducted to explore early mechanistic pathways of CN‐105 in ischemic stroke. Results: Mice receiving CN‐105 demonstrated improved survival, improved functional outcomes, reduced infarct volume, and reduced microglial activation. CN‐105 also suppressed inflammatory cytokines secretion in microglial cells in vitro. Phosphoproteomic signals suggest that CN‐105 reduces proinflammatory pathways and lower oxidative stress. Interpretation: CN‐105 improves functional and histological outcomes in a murine model of ischemic stroke via modulation of neuroinflammatory pathways. Recent clinical trial of this compound has demonstrated favorable pharmacokinetic and safety profile, suggesting that CN‐105 represents an attractive candidate for clinical translation.